Concerns Among Parents of Dental Profession Students During Covid -19 Pandemic - Dr Thippeswamy HM; Dr Ria Raj; Dr Maurya Manjunath; Nanditha Kumar M (ACHSM, 2022)
Aim: This study was undertaken to assess the concerns of the parents of dental profession students during the COVID-19 pandemic. Materials and methods: In this survey a structured questionnaire was sent to all the participants through Google Fforms. The questionnaire was designed into five sections. The complete questionnaire consisted of 19 questions. In the first section, participants needed to answer demographic information (five Questions). The second part of the questionnaire (four questions) assessed anxiety of parents and the third part was related to their professional career (three questions), the fourth part asked about effective disinfection practices (four questions) in the college premises and hostel, while the fifth part questioned about learning mode (three questions) during COVID-19 pandemic. Results: The total response rate in this present survey was 78.02%. 52.2% of parents stated that they are really anxious and have disturbed mental health. Significant percentages (more than 80%) of the parents were worried about their son/daughter's career advancement and dental profession but, 87.7% of the parents were not ready to change their son/daughter's profession. 53.2 % of the parents believed that their wards were unable to learn efficiently without attending college and 44.9 % of the parents were not satisfied in online assessment during COVID- 19 pandemic. Conclusion: Within the limitations of this present study, it was concluded that majority of the parents expressed fear and anxiety about their children's profession. Regarding the mode of learning, half of the parents expressed concern that their wards were unable to learn efficiently without attending college and clinics and also, they were unsatisfied with online assessment.